Comparing the Impact of Renewable and Non-Renewable Energy Consumption on the Economic Welfare of Iranian Provinces Using a Panel Data Approach - Mahmoud Rahimi; Mohammad Mirbagherijam; Ebrahim Ghaed; Akram Noorani (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study aims to compare the impact of renewable and non-renewable energy consumption on the economic welfare of Iranian provinces from 2000 to 2019.Methodology: The Panel Data model was used in this research. The statistical population includes research on the provinces of Iran. Time series information about these provinces has been collected from data available in the Energy Balance, Statistics Center, and Iran Economic and Financial Database, which was tested using Eviews software. Variables used in this study include consumption of renewable energy and non-renewable energy sources (solar, hydropower, wind, geothermal, oil, gas, and gasoline), economic welfare, population, labour, unemployment rate, inflation rate, income distribution inequality (Gini coefficient) and real GDP.Findings: The results showed that the consumption of renewable energy has a positive and significant impact, and the consumption of non-renewable energy has a negative and significant impact on welfare. Also, the variables of the unemployment rate, inflation rate, and income distribution inequality (Gini coefficient) have a negative and significant effect, and the variables of population growth rate, GDP, and labour productivity have a positive and significant impact on economic welfare.Originality/Value: The study showed that using renewable energy in the provinces of Iran has a more significant effect than non-renewable energy in increasing economic welfare. Investing in this production unit can improve the share of renewable energy use in Iran